2010
DOI: 10.1007/jhep01(2010)079
|View full text |Cite
|
Sign up to set email alerts
|

The large N limit of four dimensional Yang-Mills field coupled to adjoint fermions on a single site lattice

Abstract: We consider the large N limit of four dimensional SU (N ) Yang-Mills field coupled to adjoint fermions on a single site lattice. We use perturbative techniques to show that the Z 4 N center-symmetries are broken with naïve fermions but they are not broken with overlap fermions. We use numerical techniques to support this result. Furthermore, we present evidence for a non-zero chiral condensate for one and two Majorana flavors at one value of the lattice gauge coupling.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 24 publications
(33 reference statements)
3
24
0
Order By: Relevance
“…Lattice simulations with one-site or few-site large-N matrix models confirm this proposal [40][41][42], as does an earlier simulation with massive adjoint fermions [39], emulating R 3 × S 1 at N = 3. In the end, the resolution is a simple realization.…”
Section: Boundary Conditions As An Idea and Center Stability In Qcd(supporting
confidence: 70%
“…Lattice simulations with one-site or few-site large-N matrix models confirm this proposal [40][41][42], as does an earlier simulation with massive adjoint fermions [39], emulating R 3 × S 1 at N = 3. In the end, the resolution is a simple realization.…”
Section: Boundary Conditions As An Idea and Center Stability In Qcd(supporting
confidence: 70%
“…The Euclidean partition function with periodic fermions on a circle of circumference L corresponds to a twisted (non-thermal) partition function, Z(L) = tr[e −LH (−1) F ], where H is the gauge theory Hamiltonian and F is fermion number. For supersymmetric theories, like QCD(adj) with n f = 1, this is the Witten index [4] which is famously independent JHEP08(2012)063 of L. Recent work has shown that there are also non-supersymmetric gauge theories, like SU(N ) QCD(adj) with n f > 1 and with large-enough N , which do not undergo any phase transition as the radius of the circle is varied [5][6][7]. This is due to large-N volume independence: at large N an SU(N ) gauge theory on R 4 is non-perturbatively equivalent to its compactified version on T d × R 4−d , where T d is a d-dimensional torus, provided center and translation symmetries are unbroken [1,8].…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…the finite temperature case), the theory is confining at an arbitrarily small radius and the condition for volume reduction is satisfied. Following their work several papers [5][6][7][8][9][10][11][12][13][14][15][16][17] supporting the validity of volume reduction for theories with adjoint fermions were published. This observation becomes particularly interesting when combined with…”
Section: Introductionmentioning
confidence: 99%